2014
DOI: 10.1186/1471-2415-14-116
|View full text |Cite
|
Sign up to set email alerts
|

Five-year incidence of Nd:YAG laser capsulotomy and association with in vitro proliferation of lens epithelial cells from individual specimens: a case control study

Abstract: BackgroundThe aims of this study were to determine the 5-year incidence of posterior capsule opacification (PCO) requiring Nd:YAG laser capsulotomy in a representative mixed cohort of cataract patients, to determine risk factors for PCO and to investigate possible association with growth of human lens epithelial cells (HLEC) in vitro.MethodsPieces of the anterior lens capsule and adhering HLEC were obtained at cataract surgery and cultured individually. After one and two weeks respectively, cultured cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“… 1 , 4 Despite these advances, postsurgical inflammation and ocular fibrosis derived from EMT of residual LECs are still significant barriers preventing ideal visual outcomes. 9 , 100 102 Overall, this study provides new insights into the pathophysiology of cataract surgery side effects and implies that the LECs remaining behind following cataract surgery are signaling centers promoting PCS inflammation.…”
Section: Discussionmentioning
confidence: 75%
“… 1 , 4 Despite these advances, postsurgical inflammation and ocular fibrosis derived from EMT of residual LECs are still significant barriers preventing ideal visual outcomes. 9 , 100 102 Overall, this study provides new insights into the pathophysiology of cataract surgery side effects and implies that the LECs remaining behind following cataract surgery are signaling centers promoting PCS inflammation.…”
Section: Discussionmentioning
confidence: 75%
“…; Sundelin et al. ). However, with the design of the BIL‐IOL, PCO is not an issue and the hydrophilic material can be used.…”
Section: Discussionmentioning
confidence: 97%
“…The BIL-IOL implanted in the present cohort is made of hydrophilic acrylic material. Several studies have demonstrated a higher incidence of PCO in hydrophilic as compared to hydrophobic IOLs (Li et al 2013;Sundelin et al 2014). However, with the design of the BIL-IOL, PCO is not an issue and the hydrophilic material can be used.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Across studies, the reported incidence of Nd:YAG laser capsulotomy is between 2% and 67%, and the reported rates vary depending on the follow-up period and the type of IOL. 17 22 The risk of Nd:YAG laser capsulotomy is reported to be sevenfold higher with hydrophilic lenses than with the hydrophobic lenses. 11 …”
Section: Discussionmentioning
confidence: 99%